Public Partnership Program (PKM) SMP Muhammadiyah 4 Porong Sub-district Porong, District Sidoarjo, East Java - H. Hindarto; Ribangun Bamban Jakaria; Paramitha Amelia Kusumawardani; Yunianita Rahmawati (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2020)
SMP Muhammadiyah 4 Porong is one of the Muhammadiyah universities under the guidance of PCM Porong, which is located at Jl. Raya Lajuk, Dusun Pojok, Lajuk, Kec. Porong, Sidoarjo Regency, East Java 61274, is the first stepping educational institution to occupy a building within the Muhammadiyah Porong College, founded in 1966, which was originally located in the mindi sub-district, kecamatan. Porng, is a school relocation as a result of the impact of the Lapindo mudflow and until now, there are 54 students aged 12 to 15 years consisting of 3 classes, namely grades VII, VIII and IX. It has 14 teachers, consisting of 1 person as the principal and concurrently as a teacher and supported by 4 education personnel. So that the problems faced by these schools are the absence of communication media that can provide information related to the learning process, academics, student achievement and two-way communication with student guardians, teachers and schools. This aims to improve communication between teachers, guardians of students, schools and the general public. So that with the existing problems, a solution is needed so that the learning process will be achieved. So that the solution offered is to create the concept of student participation in building imagery by providing a means of actualization by building and utilizing the web as a communication medium, print and sms geetway managers, Internet Marketing training and mentoring and news coverage and writing training, so that with the solutions offered, SMP Muhammadiyah 4 Porong Sidoarjo, will be able to build self-image and communicate actual information in schools, in order to build synergy between students, parents, teachers and schools as well as the wider community.